2003
DOI: 10.1002/cncr.11561
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c‐ABL, c‐KIT, and platelet‐derived growth factor receptor‐β in ovarian serous carcinoma and normal ovarian surface epithelium

Abstract: BACKGROUND Tyrosine kinases, such as c‐KIT, c‐ABL, and platelet‐derived growth factor‐beta (PDGFR‐β), are important regulators of cell growth. Highly potent and selective inhibitors of tyrosine kinases are being investigated as alternatives to standard chemotherapy. One such inhibitor, imatinib mesylate, is being used to treat gastrointestinal stromal tumors and chronic myelogenous leukemia. Ovarian carcinomas frequently develop resistance to conventional chemotherapeutic agents. Immunohistochemical expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 51 publications
(65 reference statements)
8
64
3
Order By: Relevance
“…The simultaneous presence of PDGF b receptor and uroplakin III in the urothelium is definite proof that PDGF b receptor is expressed in epithelial cells: uroplakin expression is urothelium-specific (Sun et al, 1999) and is a highly sensitive and specific marker for urothelial tumours, including bovine urothelial neoplasias (Roperto et al, 2005). These observations are in agreement with previous reports that the receptor is expressed in cervical, ovarian and breast epithelia, among others, and in the corresponding cancers (Coltrera et al, 1995;Mayer et al, 2000;Schmandt et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The simultaneous presence of PDGF b receptor and uroplakin III in the urothelium is definite proof that PDGF b receptor is expressed in epithelial cells: uroplakin expression is urothelium-specific (Sun et al, 1999) and is a highly sensitive and specific marker for urothelial tumours, including bovine urothelial neoplasias (Roperto et al, 2005). These observations are in agreement with previous reports that the receptor is expressed in cervical, ovarian and breast epithelia, among others, and in the corresponding cancers (Coltrera et al, 1995;Mayer et al, 2000;Schmandt et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
“…Although no previous information on the expression of PDGF b receptor in bovine epithelia is available, PDGF b receptor has been found in cervical, ovarian and breast epithelia, among others, and in the corresponding cancers (Coltrera et al, 1995;Mayer et al, 2000;Schmandt et al, 2003), similar to our findings. Out of 20 neoplastic samples, 18 (90%) were positive for PDGF b receptor, T6 and T11 being the only two tumours which did not show a positive staining (Table 1; T11 shown in Figure 2s-u).…”
Section: Figuresupporting
confidence: 90%
“…Although several reports have documented the frequent PDGF/PDGFR in ovarian clear-cell adenocarcinomas S Yamamoto et al expression of PDGFRs in ovarian carcinomas, the number of clear-cell adenocarcinoma cases included in those studies was generally small. [13][14][15]17 The largest series by Matei et al 16 demonstrated that 17 (90%) and 18 (95%) of 19 clear-cell adenocarcinomas were immunohistochemically positive for PDGFR-a and PDGF-AB, respectively, the former being almost concordant with our data.…”
Section: Discussionsupporting
confidence: 90%
“…Although such mutations and gene amplification have not been described previously in ovarian cancers, recent studies have demonstrated that PDGFR-a, PDGFR-b, and PDGF-AB are commonly expressed in ovarian cancers at frequencies as high as 87, 81, and 67%, respectively. [13][14][15][16] Moreover, Henriksen et al 17 have reported that PDGFRs or PDGFs were not detected in any of the benign ovarian tumors or normal ovarian epithelium they examined. Experiments in vivo have shown that PDGFRs activated by PDGFs modulate Akt and MAPK phosphorylation and significantly influence ovarian cancer cell proliferation and tumor expansion.…”
mentioning
confidence: 95%
“…22 Several groups, including ours, reported expression of the platelet derived growth factor receptor (PDGFR) in ovarian tumors. 6,23,24 PDGFRa, but not PDGFRb, was found to be differentially expressed in ovarian carcinoma compared to normal ovarian epithelium and expression of PDGFRa was linked to poor prognosis 23 and aggressive tumor characteristics. 25,26 These preclinical findings supported the clinical investigation of PDGFR inhibitors, such as imatinib mesylate, in ovarian cancer.…”
Section: Introductionmentioning
confidence: 95%